Postoperative Adhesive Small Bowel Obstruction Risk Factors and Management in Wad-Medani Teaching Hospital - Babiker, Yasier Alayas Alkhider; Alsheikh, Ahmed Alamin (مجلة الجزيرة للعلوم الصحية; مجلد 10 عدد 1 (2014), 2014)
Background : Adhesive intestinal obstruction is a common complication of abdominal surgeries and is the commonest cause of bowel obstruction. It has high morbidity with associated poor quality of life and predisposition to repeated hospitalization. Most of them can be managed conservatively with fewer complications and a shorter hospital stay  Objectives :    To study the risk factors, the most index operation, the time relationship between operation and the onset of obstruction and outcome of postoperative adhesive Small Bowel Obstruction (SBO). Patients and Methods : This is a retrospective - prospective study of 76 patients admitted with the diagnosis of post operative adhesive intestinal obstruction. SBO was conducted by analyzing their medical records. Demographic data, clinical presentation including name, type, duration, previous surgical procedures and successful conservative approach versus requirement of operative intervention were assessed Results: Most of the patient s (68.4%) were less than 45years of age. Most of the patients were males (Male: Female 1.5:1). Most of the primary operations were emergency (80.3%), through open surgical approach (98.7%).  Appendicectomy  (46.1%), was found to be the most common cause of adhesive bowel obstruction followed by gynecological (23.7%) ,colon (14.4%).Obstruction occurs in first year in (42.1%) of patient. 46 (60.5%) patients responded to nonoperative management in 48hrs in(43.5%).30 patients needed surgery: in 14 of them surgery was needed immediately because of suspicion of   strangulation and peritonitis.In16patients surgery was performed after failure of 5days period of nonoperative trial .  Intraoperative adhesion between small bowel and scar was found to be the most common cause of obstruction (46.7%) and band adhesion was a common type in 60%.  At operation injury to small bowel occured in 10% while resection of small bowel was done in 30%. Conclusion : postoperative adhesive SBO common under 45years, M: F 1.5:1 Appendicectomy was the common primary operation, most of obstruction occured in first year. The majority of patients responded to nonoperative  management in48hrs duration .In those with suspicion of   strangulation and peritonitis or   not improved through  5days of  nonopertive  management surgery was performed .Adhesion of small  bowel to scar was the common cause of obstruction ,most of adhesions were band adhesions ,there were complications like  injury and resection of bowel.